BEST FOREIGN PRACTICES IN THE IMPLEMENTATION AND EXECUTION OF THE MECHANISM OF BENEFICIAL CREDITING OF AGRO-INDUSTRIAL COMPLEX - I. Rykova; S. Shkodinsky; A. Yurieva (Вестник Северо-Кавказского федерального университета)
The peculiarities of modern socio-economic development of Russia and its geopolitical position predetermined the choice of the agricultural sphere as a priority of modern state policy. In recent years, the problems of the development of the agro-industrial complex (hereinafter referred to as the AIC) have been actively discussed both at the legislative and the executive levels, and round tables, forums and specialized seminars are regularly held to discuss programs for the development of the agro-industrial complex, mechanisms for supporting agriculture and strengthening its material-technical base. In this regard, issues of improving tools to support agricultural producers, including taking into account the best foreign practices, are of particular relevance.